ANALISIS KINERJA UMKM DARI PERSPEKTIF PRODUKSI DAN KEUANGAN PADA UMKM PATUNG UANG KEPENG DI MAS UBUD - Ni Made Rai Juniariani; Ni Putu Sri Mariyatni; Ni Luh Putu Widhiastuti; I Gede Ngurah Sunata (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
Bali has been known as an area of ​​art with a variety of cultural characteristics and customs that are owned. Some areas in Bali have their own uniqueness with the content of local culture such as handicraft sculpture from Uang Kepeng. At first the statue of Uang Kepeng was devoted to various kinds of Hindu traditional ceremonies in Bali, but now it has been designated for commercial purposes, which is usually this statue was purchased to add luxury to the interior of the guest room, hotel / villa waiting room, or luxury restaurant. The problems faced by the two partners include: 1) Do not have a bookkeeping to calculate profit and loss, the cost of production and the recording of assets owned. 2) Do not have SOP, either related to raw materials (Uang Kepeng) or the flow in the production process. 3) The equipment which is owned by its economic age has expired so that it often suffers damage such as shaved machines, sitting drills, sensor machines, grinders, jigsaw machines, and chisels. 4) Difficulties to meet the demand for Uang Kepeng due to rare species of Kepeng. 5) The size of the showroom and production site is very narrow so it is difficult to arrange between the production site and the showroom. 6) Marketing is done only with a blog and never updated information from "Sri Kresna Wood Carver", 7) Does not have a product catalog so it is difficult to do promotions. The solutions offered to overcome these problems include: 1) Establishment and design of a bookkeeping system both profit and loss and cost of production, 2) Preparation of SOP in purchasing raw materials (Uang Kepeng) and the production process flow. 3) Arrangement of facilities for production sites. 4) Assist in finding and procuring raw materials (Uang Kepeng), 5) Procurement of some equipment that has been damaged. 6) Procurement of facilities and infrastructure that support the production activities of craftsmen. 7) Making a catalog of products owned. 8) Making promotional / marketing strategies through website creation. 9) Perform exhibitions at local and national events.